A hybrid high-gain double-pass erbium-doped fiber amplifier with dispersion compensation feedback loop - Jamaludin M.Z.; Khazani Abdullah M.; Abdullah F.; Fauzi Abas A.; Adzir Mahdi M.; Rahman F. (2023)
A new double-pass erbium-doped fiber amplifier (DP-EDFA) using chirped fiber Bragg grating (CFBG) is reported here showing a gain of 53.4 dB and noise figure (NF) of 5.36 dB. The proposed amplifier at the same time provides dispersion compensation through the use of CFBG. 2007 Elsevier Ltd. All rights reserved.